The effects of self-management intervention based on Information-Motivation-Behavioral model in patients receiving targeted therapy for lung cancer (基于IMB模型的自我管理干预在肺癌靶向治疗患者中的应用) - ZHANG Junli (张俊丽); ZHAO Jian (赵健); JING Dan (井丹); AN Juan (安娟); HAN Lijun (韩丽军) (中西医结合护理)
Objective To investigate the effect of self-management intervention based on Information-Motivation-Behavioral (IMB) model in the patients with advanced lung cancer receiving targeted therapy. Methods A total of 102 patients with advanced lung cancer receiving targeted therapy in a tertiary grade A hospital were divided into study group (n=51) and control group (n=51) according to the sequence of hospital admission. The patients in the control group were provided with routine intervention, while patients in the study group were treated with the self-management interventions based on the IMB model. The disease knowledge level, self-management skills and quality of life were evaluated before intervention and one month after discharge. Results The scores of disease knowledge questionnaire, Strategies Used by People to Promote Health (SUPPH)and Generic Quality of Life Inventory-74 (GQOLI-74) were decreased in both two groups after intervention, and scores of relevant assessment in the study group were higher than those in the control group(P＜0. 05). Conclusion The self-management interventions based on IMB model can effectively improve lung cancer patients' self- management ability and quality of life during targeted therapy. (目的 分析基于信息-动机-行为技巧(IMB)模型的自我管理干预在肺癌靶向治疗患者中的应用效果。方法 选取2021年3月—2022年3月医院住院的肺癌靶向治疗患者102例, 按患者住院时间分为对照组和干预组, 其中2021年3月—9月收治的51例患者为对照组, 2021年10月—2022年3月收治的51例患者为干预组。对照组患者接受常规护理干预, 干预组患者在对照组基础上实施基于 IMB 模型的自我管理干预, 两组患者干预时间均为1个月。分别于入组时、干预后1个月时评估两组患者疾病知识水平、自我管理能力和生活质量。结果 干预后, 两组疾病知识调查问卷、癌症自我管理效能感量表(SUPPH)和生活质量综合评定问卷(GQOLI-74)得分较干预前上升, 且干预组疾病知识调查问卷、SUPPH量表和GQOLI-74问卷得分高于对照组, 差异有统计学意义(P＜0. 05)。结论 基于IMB模型的自我管理干预可改善肺癌靶向治疗患者自我管理水平, 提升患者生活质量。)